THE EFFECT OF COMPETENCY AND ASSESSMENT OF EMPLOYEE PERFORMANCE ON PROMOTION AT PT. BUKIT ENERGI INTEGRATED SERVICE - Erdiansyah, Erdiansyah; Usman, Benny; Purnamasari, Rati (Dynamic Management Journal, 2024)
PT. Bukit Energi Servis Terpadu (BEST) is a company engaged in Operation & Maintenance (O&M) services under the PT Bukit Asam Tbk group. This research was conducted with the aim of determining the effect of competence and assessment of employee performance on job promotion. The quantitative method was chosen by researchers to conduct this study using primary data in the form of observations and questionnaires with respondents as many as 60 employees. Data analysis techniques used include multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and F test with data processing using SPSS software program version 21. Based on the results of the t test conducted, there is an influence of competence on job promotion, meaning that partially competence affects job promotion. Meanwhile, the assessment of employee work performance on job promotion means that partially the assessment of employee work performance affects the promotion of positions at PT. Hill Energy Integrated Service. From the results of the F test, Ho was rejected and Ha was accepted. So it can be concluded that there is a significant relationship between competence and employee performance assessment of promotion at PT. Hill Energy Integrated Service.